2x(9-x)=

Simple and best practice solution for 2x(9-x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(9-x)= equation:


Simplifying
2x(9 + -1x) = 0
(9 * 2x + -1x * 2x) = 0
(18x + -2x2) = 0

Solving
18x + -2x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2x'.
2x(9 + -1x) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9

Solution

x = {0, 9}

See similar equations:

| 8(n+8)=-8(-5n+1)+4n | | 27m-7m=40 | | 15x=3y+6 | | 8y-62=-y-8 | | 60x-153=9x | | 0.05(n+10)=0.95 | | 12r+17r= | | ((5x+10)+1)=4x | | 4c-7=37 | | -25-11x=-6x | | -12=9+-7x | | -4(n+3)+3=-3n-3(3-n) | | 9+(3b+8)=(3b+8+9) | | 216x^4-600x^2=0 | | 3x+5x-2=4x-10 | | 2x+3=-11+4x | | 5d+3d+2d-4d=12 | | x^2+26+160=0 | | 4*-9-70=12*-9+2 | | -2+7x=5(-6+7) | | -3(7v+5)+7v=-5+3(v+8) | | 12r+17r=105 | | 2x+2x+3x-2+3x-2=3x-1+3x+3x+1 | | 9-2y=-11+6 | | -6=2n-3n | | 30y^3+28y^2-16y=0 | | 5y+9+119=180 | | 5(3)+2y=10 | | -17=-4x+3 | | 11-7(12k+2)=-(3-4k)-3k | | 2g+3(-7+2g)=1-9 | | .50x+.35(70)=44.5 |

Equations solver categories